Modeling Water Erosion in Wadi Al-Sadr Basin by Applying the Revised Universal Soil Loss Equation (RUSLE) - الزهراني, افراح (Journal of King Abdulaziz University: Environmental Design Sciences, 2025)
The study aims to estimate the volume of water erosion in Wadi Al-Sadr basin by applying the global equation model (RUSLE), using remote sensing data and geographic information systems. To achieve this aim, study methodology gradated from reviewing the literature to know criteria for applying this model such as rainfall-runoff erosivity, topography, soil erodibility, cover- management, and support practice. Then start collecting data for these criteria from several sources and processing these data in preparation for deriving the informational layers for each criterion. Then applying (RUSLE) model equation in geographic information systems environment to estimate annual erosion volume in basin and classify it according its risks. The results of study concluded that volume of soil water erosion in Al-Sadr wade basin ranged between 0 - 3357.9 tons/ha/ year, with an average 2.2 tons/ha/year at spatial level of basin. The results showed that most of basin has a volume of erosion less than 0.5 tons/ha/ year, an area 307.75 km2, by 74.91% of basin area. The area characterized by water erosion ranging between 0.5 - 5 tons/ha/year covers 54.21 km2, by 13.2% of basin area. While area of zone where soil erosion ranges between 5-10 tons/ha/year is 16.68 km2, by 4.06% of basin area. The area of zone in which volume of water erosion ranges between 10-15 tons/ha/year is 8.67 km2, by rate of 2.11% of basin area, and area of zone where volume of soil water erosion exceeds 15 tons/ha/year is reached 23.53 km2, by 5.72% of total basin area.